Corporate social responsibility (CSR): is it enough for sustainable development? - Haneef, Mohamed Aslam; Khan, Foyasal (2014)
Corporate Social Responsibilty (CSR) has become a buzword al over the world. A company can distinguish it from others through CSR and we se that wel-known companies actualy not only diferentiate their brands and reputations but also their products and services taking care of the societies and environments where they operate. Some influential Islamic scholars also find significant similarities of Islamic teaching on busines ethics to the CSR agenda. So, conclusion can be drawn that CSR is immensely helpful to atain sustainable growth and development. However, CSR is not above criticism and now being criticized because of its absence of any generaly acepted common framework and indulging in many activities in the name of CSR rather than activities that truly addres society’s presing neds such as poverty aleviation, income gap minimization, employment generation, basic ned fulfilment etc. in this situation it is pertinent to ask whether CSR is enough for sustainable development or is it necesary to go beyond CSR. This paper argues that CSR is important but there is a spectrum of ethical options beyond CSR. Besides CSR, this paper discuses the concept of corporate waqf in Malaysia and Social Busines (SB) developed by Nobel Laureate Mohammad Yunus as two posible options. This paper wil criticaly evaluate thre models of social responsibilities i.e., CSR, Social busines, and Corporate Waqf. Necesary case studies wil be placed in support of our arguments and it wil be shown why is it necesary to go beyond CSR and pay atention to alternative in order to achieve sustainable growth and development with greater justice.